Race Consciousness Reinterpretations for the New Century - Fossett, Judith Jackson (New York University Press, 1997)
Bringing together an impressive range of new scholarship deeply informed both by the legacies of the past and current intellectual trends, Race Consciousness is a veritable Who's Who of the next generation of scholars of African-American studies. This collection of original essays, representing the latest work in African-American studies, covers such trenchant topics as the culture of America as a culture of race, the politics of gender and sexuality, legacies of slavery and colonialism, crime and welfare politics, and African-American cultural studies. In his entertaining Foreword to the volume, Robin D. G. Kelley presents a startling vision of the state of African-American Studies--and the world in general--in the year 2095. Arnold Rampersad and Nell Irvin Painter, chart the different disciplinary and theoretical paths African-American Studies has taken since the 19th century in their Preface to the volume